Harnessing photocurrent enhancement in silver-bacterial cellulose nanocomposite for ultra-sensitive Hg2+ electrochemical detection - Pooja Deshpande; Shashwati Wankar; Rutuja Gumathannavar; Snehal Kulkarni; Yogesh Jadhav; Yogesh Patil; Jyutika Rajwade; Atul Kulkarni (Nanocomposites, 2024)
Global health and ecosystem concerns over mercury pollution require stringent monitoring. Herein, we showcase a novel approach for detecting trace Hg2+ ions in water using cyclic voltammetry (CV). Our approach involves modifying glassy carbon electrode (GCE) and screen printed electrode (SPE) surfaces with a nanocomposite of ascorbic acid-capped silver nanoparticles (AsAgNPs) embedded in nanocrystalline bacterial cellulose (AsAgNP-NBC). Analytical techniques confirmed the nanocomposite’s stability and morphological characteristics, exhibiting high accuracy within a linear range of 10 nM to 1 µM Hg2+ and a low limit of detection (LOD) of 3.531 nM. Additionally, on irradiation with 455 nm light source, AsAgNP-NBC modified SPE displayed a remarkable 9.6 times enhanced photocurrent, achieving an LOD of 3.95 pM, and enhanced photoresponsivity of 55.2 mA W−1, showcasing its potential for ultra-trace level detection. This cost-effective and biocompatible nanocomposite presents a promising alternative to conventional analytical methods for selective detection of trace Hg2+ ions in environmental samples.